Paleographic Style and the Forms and Functions of the Dead Sea Psalm Scrolls: A Hand Fitting for the Occasion? - Longacre, Drew ca. 21. Jh. (Vetus Testamentum, 2022)
In this article I apply stylistic paleographic analysis to the Dead Sea Psalm scrolls, proposing conventional usage registers for different types and levels of scripts. I argue that more formal scripts were normally used for large presentation copies of known versions of the Davidic psalter, while less formal scripts were frequently used for smaller, textually distinctive manuscripts. This observation aids in the interpretation of the forms and functions of the majority of Dead Sea Psalm scrolls that follow this pattern and highlights exceptional cases worthy of further investigation.